Makna Patriotisme dalam Lirik Lagu Rock Indonesia: Kajian Semiotik Charles Sanders Pierce - Hajriyo, Hajriyo; Pangesti, Nesa Riska (Persona: Kajian Bahasa dan Sastra, 2024)
This study aims to construct the meaning of patriotism in Indonesian rock song lyrics using Charles Sanders Pierce's semiotic approach. The analyzed songs are "Jadilah Legenda" by Superman Is Dead, "Garuda di Dadaku" by Netral, "Bendera" by Cokelat, and "Dari Mata Sang Garuda" by Pee Wee Gaskins. This research employs a descriptive qualitative method by analyzing the song lyrics based on Pierce's semiotic theory, which divides signs into trichotomies: qualisign, sinsign, and legisign; as well as icon, index, and symbol; and also rheme, dicent sign, and argument. The results show that Indonesian rock song lyrics have complex and rich forms and meanings of patriotism. Through the use of semiotic signs, the lyrics not only express love and pride for the homeland but also invite listeners to actively participate in preserving and fighting for national values. This study provides significant contributions to understanding how Indonesian rock music can serve as a medium for expressing patriotism and a tool to inspire collective action within society